2015
DOI: 10.1007/s00268-015-3252-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesh Location in Open Ventral Hernia Repair: A Systematic Review and Network Meta‐analysis

Abstract: There is no consensus on the ideal location for mesh placement in open ventral hernia repair (OVHR). We aim to identify the mesh location associated with the lowest rate of recurrence following OVHR using a systematic review and meta-analysis. A search was performed for studies comparing at least two of four locations for mesh placement during OVHR (onlay, inlay, sublay, and underlay). Outcomes assessed were hernia recurrence and surgical site infection (SSI). Pairwise meta-analysis was performed to compare al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(182 citation statements)
references
References 42 publications
8
153
0
21
Order By: Relevance
“…However, in a cohort study, Gleysteen (17) reported that onlay and sublay mesh repair techniques have similar wound complication rates (16% and 12%, respectively). In a recent meta-analysis, sublay mesh repair was reported as having the least wound infection rate than onlay, inlay, and underlay mesh placement [Odds Ratio: 0.449 (95% CI, 0.12-1.16)] (19). In the present study, the mean operation time was shorter in the onlay group and the mean complication rate was lower in the sublay group.…”
Section: Incisional Hernia Remains a Major Problem After Laparotomysupporting
confidence: 58%
“…However, in a cohort study, Gleysteen (17) reported that onlay and sublay mesh repair techniques have similar wound complication rates (16% and 12%, respectively). In a recent meta-analysis, sublay mesh repair was reported as having the least wound infection rate than onlay, inlay, and underlay mesh placement [Odds Ratio: 0.449 (95% CI, 0.12-1.16)] (19). In the present study, the mean operation time was shorter in the onlay group and the mean complication rate was lower in the sublay group.…”
Section: Incisional Hernia Remains a Major Problem After Laparotomysupporting
confidence: 58%
“…It is most likely due to a selection bias. Anecdotal evidence from this centre suggests increasing use of the sublay technique in line with recent evidence [18], particularly among surgeons doing relatively higher numbers.…”
Section: Resultssupporting
confidence: 68%
“…While repair of ventral hernias with mesh is considered routine, there is no consensus on the best location to place the mesh. [10][11][12] When considering the best location for mesh placement, a number of features are important to consider. First, mesh tissue integration may reduce long-term recurrence with theoretically improved rates with greater mesh-tissue overlap.…”
Section: Resultsmentioning
confidence: 99%
“…Sublay repair allows for tissue integration from two loadbearing tissues from both sides-Posterior rectus sheath and the anterior myofascial complex. [10][11][12] In addition, sublay mesh placement protects the mesh from exposure from superficial wound complications, intra-abdominal adhesions and contamination. Creation of DE vascularising skin flaps is avoided.…”
Section: Resultsmentioning
confidence: 99%